The Role of Ultrasound and Magnetic Resonance Imaging in the Assessment of Musculo-Tendon Pathologies of the Shoulder Joint - Khamidov Obid Abdurakhmanovich, Davranov Ismoil Ibragimovich, Ametova Alie Servetovna (Scholars Digest Publishing, 2023)
Goal:to assess and characterize musculo-tendon pathologies of the shoulder joint using ultrasound (US) and magnetic resonance imaging (MRI). Background and goals: The shoulder joint, being the most mobile and unstable of all joints, is often prone to injury. To compensate for the unstable bone anatomy, the shoulder is protected from the front, back, and top by a capsule and tendons forming the rotator cuff of the shoulder. Ultrasound is often considered the first-line imaging method for evaluating the cuff, as well as for diseases unrelated to the rotator cuff. MRI is important in cases of extensive abnormalities that are often not fully characterized at the initial sonographic examination, as in the case of sonographically inaccessible areas. However, musculoskeletal imaging is indeed a multi-modal approach, and a combination of techniques should be used to identify and characterize the lesion.
Keywords: magnetic resonance imaging; rotator cuff; ultrasound.